Studies Regarding the Meat Quality of the Specie Clarias Gariepinus - Adela Marcu; Ileana Nichita; Adrian Marcu; Cornelia Vintilă; Maria Nicula; Dorel Dronca; Cristian Roman; Kelciov Bartolomeu (Scientific Papers Animal Science and Biotechnologies, 2023)
The chemical composition of the meat is one of the most important characteristics. For the fish meat quality there are only few specific data comparatively with those that exist about animal meat. The results obtained from a study done on the meat quality of the fish specie Clarias gariepinus (African catfish) with a body weight of around 1200 – 1550g are presented in this paper. The obtained results emphasized a great quality of the Clarias gariepinus meat. The meat proteins content had a big value and it was indirectly proportional to the body weight. The meat hydration was higher in fishes with low body weight and indirectly proportional to the fat content. Taking in consideration the fat content of this meat, it can be concluded that the African catfish could be included in the half fat fish category. The meat caloricity calculated is growing proportionally to the body weight, being influenced by the fat content.